Application of Color Play with Yarn Media to Develop Children's Creativity in PAUD Nurul Iman - Indriani, Soneta; Manto (International Journal Education and Computer Studies (IJECS), 2024)
Children's creativity can be developed through play because if balanced with play, children can learn to control themselves. Therefore, this study plans to find out whether colour plays with yarn media can develop early childhood creativity in PAUD Nurul Iman, Talang Baru Village, Pajar Bulan District, and find out the supporting and inhibiting factors in the development of early childhood creativity through colour play. The research method used in this study is Classroom Action Research, which is research conducted in a class to determine the consequences of actions applied to a research subject in that class. Based on the results of research conducted for two cycles and each cycle carried out for three meetings, it can be concluded that the increase in creativity in PAUD Nurul Iman children, Talang Baru Village, Pajar Bulan District, Lahat Regency occurred because of learning carried out through colouring activities with yarn media. This is shown by the increase in children's creativity in each cycle. Based on the data in this study, the creativity of PAUD Nurul Iman children, Talang Baru Village, Pajar Bulan District, Lahat Regency, in each cycle has increased to 80.6% of 21 children.